2010
DOI: 10.1016/j.jalgebra.2010.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Sections of homogeneous vector bundles

Abstract: In this work we give a method for computing sections of homogeneous vector bundles on any rational homogeneous variety G/P of type ADE. Our main tool is the equivalence of categories between homogeneous vector bundles on G/P and finite dimensional representations of a given quiver with relations. Our result generalizes the work of Ottaviani and Rubei (2006) [OR06].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Moreover, with the previous notations, we have det(U ) = det(L) ⊗ U /L, det(U ) = det(L) ⊗ U /L, and the quadratic form induces a natural duality between U /L and U /L. From this one easily deduces that p * (1). And then…”
Section: C Uniquenessmentioning
confidence: 86%
See 2 more Smart Citations
“…Moreover, with the previous notations, we have det(U ) = det(L) ⊗ U /L, det(U ) = det(L) ⊗ U /L, and the quadratic form induces a natural duality between U /L and U /L. From this one easily deduces that p * (1). And then…”
Section: C Uniquenessmentioning
confidence: 86%
“…The half-spin representations are self dual when n is even, and dual one to the other when n is odd. It follows from the usual Bruhat decomposition that the Chow ring of S ± is free, and the dimension of its k-dimensional component is equal to the number of strict partitions of k with parts smaller than n. In particular the Picard group has rank one, and L is a generator; we therefore denote L = O S ± (1). We also let U be the rank n vector bundle obtained by restricting the tautological bundle of G(n, 2n).…”
Section: Spinor Varieties 2a Pure Spinorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence one has the following result. We will apply Theorem A of [3], which in this context says that if for some i = h + 1, . .…”
Section: Global Sections Of P K O(d) and Taylor Truncation Mapsmentioning
confidence: 99%
“…In 1988, Purohit 48 HÜLYA KADIO ¼ GLU [13] showed that there is a one-to-one correspondence between homogeneous vector bundles and linear representations. Various other studies about homogeneous vector bundles can be found in the literature ( [2], [8], [11]). Moreover, in 1972 R. W. Brockett and H. J. Sussmann described how the tangent bundle of a homogeneous space can be viewed as a homogeneous space [5].…”
Section: Introductionmentioning
confidence: 99%